Building Assertive Character through the Arabic Picture Storybook - kurniawan, Bobby; Liza, Fitri (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
Human creativity extensively uses language to transform values, particularly through picture storybooks. "Qissat Asḥāb al-Fīl" (The Story of the Elephant Army) by Muhammad Abbas Al-Mubarak narrates the Asḥāb al-Fīl story, embedding various values, notably assertiveness. This study employs a descriptive qualitative analysis using content analysis to examine assertive characteristics in the storybook. Through denotative and connotative approaches, thirteen sentences exhibiting assertive traits were identified; eight sentences describe courage, one sentence describes responsibility, and four sentences describe desire. The findings indicate that "Qissat Asḥāb al-Fīl" promotes assertiveness, crucial for children's character development. This research underscores the potential of storybooks in fostering assertive behavior by enhancing readers' understanding of communication and recognizing linguistic nuances that convey assertiveness. Thus, this study contributes to the discourse on the educational value of storybooks in character building.